2019
DOI: 10.1097/pai.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Does Argininosuccinate Synthase 1 (ASS1) Immunohistochemistry Predict an Increased Risk of Hemorrhage for Hepatocellular Adenomas?

Abstract: Hepatocellular adenomas (HCAs) often pursue an innocuous clinical course. Recent work has elucidated important subtypes of HCA and biomarkers to identify them, including HCA at an increased risk for malignant transformation. Another key complication of HCAs is the risk of spontaneous tumoral hemorrhage, which may be life-threatening. Identification of a predictive biomarker for this clinical complication would therefore be of clinical value. It has been suggested that Argininosuccinate Synthase 1 (ASS1) immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although some found immunohistochemical expression of Argininosuccinate Synthase 1 (ASS1) to identify in unclassified HCA a subgroup with a high risk for bleeding, others found no such correlation. 12 A more recently described subtype is sonic hedgehog (sh) activated HCA (5% of HCAs), which is frequently identified in obese patients and may…”
Section: Subtypes Of Hcamentioning
confidence: 99%
See 1 more Smart Citation
“…Although some found immunohistochemical expression of Argininosuccinate Synthase 1 (ASS1) to identify in unclassified HCA a subgroup with a high risk for bleeding, others found no such correlation. 12 A more recently described subtype is sonic hedgehog (sh) activated HCA (5% of HCAs), which is frequently identified in obese patients and may…”
Section: Subtypes Of Hcamentioning
confidence: 99%
“…HCAs not demonstrating any of the specific earlier phenotypes are considered “unclassified.” These represent 5% to 10% of HCAs. Although some found immunohistochemical expression of Argininosuccinate Synthase 1 (ASS1) to identify in unclassified HCA a subgroup with a high risk for bleeding, others found no such correlation 12 . A more recently described subtype is sonic hedgehog (sh) activated HCA (5% of HCAs), which is frequently identified in obese patients and may be associated with increased risk for bleeding 13 .…”
Section: Hepatocellular Adenomamentioning
confidence: 99%
“…In a recent paper, ASS1 IHC positivity (without comparison to NT liver in 57% of cases) was not found to correlate with hemorrhage, whatever the HCA subtype. ( 21 ) It is quite obvious that all HCA subtypes can bleed. In this work, our purpose was to identify, using ASS1 overexpression, shHCA that are known to be at high risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…ASS1 positivity without overexpression in different HCA subgroups has been reported and has created confusion about the pertinence of ASS1 as an immunomarker. ( 19,21 )…”
mentioning
confidence: 99%
“…While there are no specific histopathologic features in this HCA subtype, it seems that prostaglandin D synthase and argininosuccinate synthase 1 (ASS1), particularly ASS1 positivity by immunohistochemistry is a hallmark of shHCA[ 2 , 33 ]. Although ASS1 may be expressed in other HCA subtypes with hemorrhage and thought to be a marker of hemorrhage[ 34 ], a recent study showed ASS1 expression did not correlate with HCA hemorrhagic complications[ 35 ]. Interestingly, higher risk of hemorrhage has been consistently observed both histologically and clinically in shHCA[ 2 , 31 ].…”
Section: Hca: Morpho-molecular Classificationmentioning
confidence: 99%